Examining user perspective of an online learning resource for physiotherapists: A mixed methods study of the TRAIN program. (31st May 2021) - Scrivener, Katharine; Akkermans, Jake; Svanetti, Sean; Szilas, Chloe; Robson, Matthew; Love, Sherrie
Abstract: Background: Implementing task specific training is a commonly reported challenge for less experienced therapists. A potential method to improve the ability of recent graduate and student therapists is to upskill regarding task specific training via an online education resource. Purpose: To evaluate the use and acceptability of the TRAIN program as an online learning resource for physiotherapists. Methods: Data from Google Analytics was sourced to determine use of the program and details about the users. Users of the TRAIN program were also invited to complete two surveys; prior to beginning and upon completion of the program. The surveys collected information about the demographics of the users, perceptions of usefulness of the online resource and overall sentiment. Results: Almost 6000 new users interacted with the TRAIN modules during the 15‐months study period. The surveys indicated a high level of usability (mean score 9/10, SD 1.5) and clinical utility (mean score 8.8/10, SD 1.6) of the TRAIN program. Perceived knowledge and user confidence in implementing task‐specific training was higher for those users completing the post compared to those completing the pre‐module survey (knowledge 1.9 and confidence 1.7 out of 10 points higher). Recurring comments in the open‐ended feedback pertained to the usefulness, clarity, and ease of use of the TRAIN program. Discussion and Conclusion: This study provides preliminary evidence supporting the use and acceptability of the TRAIN program as an online learning resource for physiotherapists. This further contributes to the growing body of literature indicating online learning is generally a well‐received teaching tool for physiotherapists.